Pilkada dan Sinergi Perencanaan Pembangunan antar Pemerintah daerah: Peran Gubernur yang Nyata tapi Tak Kentara - Zarida Hermanto; Joko Suryanto (Institut Pemerintahan Dalam Negeri (IPDN), 2016)
Local election which is implemented since 2004 have contrast paradigm in new orde. Governor as local head in province level is elected by the people beside city’s head and regency’s head. Governor as province head has three primary functions namely coordination, supervision, and control. Those functions is used to synergize regency and citi’s development planning in order to make sustainable development. In implementation process, governor’s function is not effective to synergize city’s head and regency’s head. This paper explained about the “functionless of governor” to make development in province as local and city’s development in order to suitbale with province development plan